Management criteria evaluation of lithuanian football academies` certification system - Vegys, K.; Bagdoniene, R.; Jonaitiene, D.; Valantine, I. (Baltic Journal of Sport and Health Sciences, 2023)
Background. There is a tendency in the football environment to assess and classify youth football organisations on a national scale to make their activities more efficient, raise the level of football and talent development, and increase competition in the context of international football. Considering the practices of Georgia and Latvia, Lithuania has started testing the certification of football academies since 2021. During the testing stage, it was observed that the certification project helped youth football organisations to improve the quality of their activities and competencies - after a year, the certification system was started to be applied to all Lithuanian football academies. As of 2022, higher certification criteria have been applied to football organisations, which the future of our country depends on.